Walking Ability and Quality of Life in Subjects With Transfemoral Amputation: A Comparison of Osseointegration With Socket Prostheses - Van de Meent, Hendrik; Hopman, Maria T.; Frölke, Jan Paul (Archives of physical medicine and rehabilitation, 2013)
To investigate walking ability and quality of life of osseointegrated leg prostheses compared with socket prostheses. Prospective case-control study. University medical center. Subjects (N=22) with transfemoral amputation (1 bilateral) referred to our center because of socket-related skin and residual limb problems resulting in limited prosthesis use. Their mean age was 46.5 years (range, 23–67y) and mean time since amputation was 16.4 years (range, 2–45y). Causes of amputation were trauma (n=20) and tumor (n=2). Implantation of an osseointegration prosthesis (OIP). Global score of the Questionnaire for Persons With a Transfemoral Amputation (Q-TFA), prosthesis use, 6-minute walk test (6MWT), Timed Up & Go (TUG) test, and oxygen consumption during treadmill walking. With the socket prosthesis, the mean ± SD Q-TFA global score, prosthesis use, 6MWT, TUG, and oxygen consumption were 39±4.7 points, 56±7.9h/wk, 321±28m, 15.1±2.1 seconds, and 1330±310mL/min, respectively, and significantly improved with OIP to 63±5.3 points, 101±2.4h/wk, 423±21m, 8.1±0.7 seconds, and 1093±361mL/min, respectively. Osseointegration is a suitable intervention for persons whose prosthesis use is reduced because of socket-related problems. Subjects with OIP significantly increased their walking ability and prosthesis-related quality of life.